Photographic manipulation in the health, clinical and biomedical sciences. (1st April 2019) - Schneider, Catherine; Hoffmann, Sydney; Rowles, Graham D.
AbstractPhotography has become a pervasive component of contemporary communication. Recent technological advances in creating and manipulating images have provided renewed impetus to decades-long debates on use of photographs in science. With increase in the potential for inappropriate image manipulation, fears about misrepresentation have heightened concern among journal editors and scholars about the 'accuracy' of published images. We discuss how science has responded to growing concerns surrounding falsification and inaccuracy of photography. We document progress in implementing a variety of complementary approaches to addressing the problem. These include digital forensics, photo member checking and the implementation of codes of ethics to enhance the veracity of published photographs in science research. We conclude by acknowledging the irreducible conflict likely to remain between use of the photograph as a creative work of art and employment of this medium as a source of information in the progress of science.